COMPARISON OF DEXMEDETOMIDINE VERSUS FENTANYL IN UNILATERAL SPINAL ANESTHESIA, IN LOWER LIMB ORTHOPEDIC SURGERIES: RANDOMIZED CONTROL TRIAL - Mamoona Shaikh; Muhammad Anwaar-ul-Hassan Khan; Kelash Kumar; Ahmed uddin Soomro; Pardeep Kumar; Maqsood Ahmed Siddiqui (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
OBJECTIVE: To investigate the impact of intrathecal bupivacaine and Dexmedetomidine and fentanyl on the strength and duration of blocks during lower limb orthopedic procedures.BACKGROUND: While general, neuroaxial, or local anesthesia can be used for lower limb surgeries, neuroaxial block is the recommended method. Quick onset and cost-effectiveness are all provided by spinal block.STUDY DESIGN: A randomized controlled trialPLACE AND DURATION: This study was conducted in Liaquat University of Medical and Health Sciences Jamshoro from March 2023 to March 2024METHODOLOGY: A total of 60 persons who were booked for lower limb surgery due to any indication were randomly assigned to two groups (A and B) consisting of thirty patients each, using single blind randomization. Group A received 2.5 milliliters of hyperbaric bupivacaine plus 25 micrograms of fentanyl (0.5 milliliter) and group B received 2.5 milliliters of hyperbaric bupivacaine plus 10 micrograms of DEX (0.5 milliliters) of unilateral spinal anesthesia. SPSS version 26.0 was used to enter and analyze the data.RESULTS: According to our findings, the mean duration of the surgery was 2.44 ± 0.62 and 2.14 ± 0.43 for A and B group. The mean age of the participants was   45.67 ± 5.22 and 43.5 ± 6.76. Mean BMI of the participants was 27.12 ± 3.12 and 26.9 ± 3.71 for A and B group respectively. Time to rescue analgesia, frequency of analgesic demand, and total nalbuphine dosage differed significantly between the two groups.CONCLUSION: In lower limb procedures, intrathecal Dexmedetomidine (10 μg) appears to be a more effective option than fentanyl (25 μg) for achieving desirable results in unilateral spinal anesthesia, with fewer side effects and better post-operative analgesia.